Acute caffeine ingestion improves sport-specific and cognitive performance in elite badminton athletes - Feng, L.; Du, W.; Wang, X.; Cao, H.; Ji, Z.; Li, F.; Cao, J.; Zhou, Z. (Frontiers in Nutrition, 2025)
Background: Caffeine, a widely used central nervous system stimulant, has been extensively studied for its potential to enhance exercise performance. However, systematic evaluations of its effects on badminton-specific performance remain limited, particularly in the domains of cognitive function and technical skills.